Unveiling the brain mechanism underlying depression: 12 Years of insights from bibliometric and visualization analysis - Donghai Wu; Siying Qu; Haiju Sun; Shuting Zhou; Xinyuan Qu; Yutian Chen; Hantong Hu; Xiaoyu Li (Brain Research Bulletin)
Depression is a common but serious mental health illness affected human’s physiology and psychology. In contemporary times, neurophysiological research on depression has emerged as a prominent area of investigation, yet there remains a paucity of review elucidating the central mechanisms of depression in the brain. Consequently, we undertook a bibliometric analysis and visualization assessment to underscore recent advancements in research pertaining to the neural underpinnings of depression. By employing these methods, we have collected articles spanning the period from 2013 to 2024, shedding light on the latest insights into the brain mechanisms associated with depression. Bibliometric analysis found 16327 research papers in the field of brain mechanism underlying depression, overall showing a sustained growth trend. Through meticulous analysis of collected data on institutions and countries, authors, co-cited literature, keywords, etc., this paper humbly aims to tentatively identify future research hotspots and frontiers, hoping to modestly contribute to and stimulate further scholarly progress in the field.